Use of reinforced ceramics for slabs in an autarchy period. Pathology and intervention strategies. (December 2020) - Serrrano-Lanzarote, Begoña; Cerdán-Castillo, Vicente; Ortega-Madrigal, Leticia; Almerich-Chulia, Ana
Abstract: This article highlights the possibilities offered by reinforced ceramics during three decades of the last century to shape horizontal structures of buildings in Spain. A historical context of lack of basic building materials, the ability to assemble forged with cseramic pieces was successfully exploited. Without limiting the number of buildings that needed to be rehabilitated and built, this shortage led the authorities to restrict the use of iron, reserving the small quantities available for those parts of the construction where its role could hardly be replaced. The authorities promoted its use by standardising it, together with other construction techniques. The current commitment of the authorities to the rehabilitation of the obsolete residential park makes it necessary to know how the buildings were constructed in the past in order to propose efficient intervention strategies. In this sense, the construction system presented here arises from the current inspections of building structures in the Community of Valencia, Spain. In addition, the article presents the most frequent pathology detected in this type of slabs and proposes reinforcement strategies considering the products and systems currently available with the final objective of guaranteeing their recovery and prolonging their useful life.